El juego motor en el desarrollo de las nociones espaciales en los niños y niñas de 4 a 5 años en el centro de educación inicial Teresa León de Noboa, cantón Guaranda, provincia Bolívar, año 2023 - Avilés Veloz, Lenin Fernando (2024)
The objective of the degree work is to establish the importance of motor play in the development of spatial notions of children from 4 to 5 years of age, at the Teresa León de Noboa Initial Education Center, Guaranda cantón, Bolívar province, year 2023. It can be determined that the game is a fundamental activity for an effective integral development of the boys and girls in Initial Education because the learning in the first years of life has its origin in the game. We work with the theme The motor game in the development of spatial notions of children from 4 of 5 years old, because it can be observed that in the Teresa León de Noboa Initial Education Center there are series of limitations for its execution. Although the teachers express that they do. For the investigative work, the qualitative – quantitative approach was used, because it was possible to analyze the quality of the activites carried out by the boys and girls, the materials or resources used, the relationshisps that occur during the game and the spatial notions, the design was cross – sectional, because the investigation fulfills a determined, specific time; the type of study was exploratory because the situation of boys and girls in relation to the development of spatial notions was analyzed, Regarding the methods, we worked with the inductive, deduective, analysis – synthesis, bibliographic and action research. As techniques, a survey with 10 closed quiestions was applied to the teachers, while an observation sheet was applied to the children. As conclusions that the motor game is of great importance as a strategy, in the development of spatial notions of children from 4 to 5 years old, because it allows the integral development of the boy ans girl, it also allows them to socialize with others, create a series of values for a harmonious coexistence. The games of laterality, distances, locations, positions are of great value for the development of the spatial notions in boys and girls from 4 o to 5 years